2013
DOI: 10.1371/journal.pone.0056891
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Regulated Kinase 1/2 Signaling Is a Critical Regulator of Interleukin-1β-Mediated Astrocyte Tissue Inhibitor of Metalloproteinase-1 Expression

Abstract: Astrocytes are essential for proper central nervous system (CNS) function and are intricately involved in neuroinflammation. Despite evidence that immune-activated astrocytes contribute to many CNS pathologies, little is known about the inflammatory pathways controlling gene expression. Our laboratory identified altered levels of tissue inhibitor of metalloproteinase (TIMP)-1 in brain lysates from human immunodeficiency virus (HIV)-1 infected patients, compared to age-matched controls, and interleukin (IL)-1β … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 53 publications
1
20
0
1
Order By: Relevance
“…C/EBPβ knockdown decreased COX-2 mRNA and protein levels, while it increased BDKRB2 mRNA expression. Data from a related study show p38K inhibition blocks IL-1β-mediated astrocyte C/EBPβ expression, whereas ERK1/2 inhibition enhances expression [8]. Accordingly, we found that the IL-1β-mediated increase in COX-2 expression is p38K-dependent, whereas IL-1β-mediated expression of BDKRB2 is ERK1/2-dependent.…”
Section: Discussionsupporting
confidence: 60%
“…C/EBPβ knockdown decreased COX-2 mRNA and protein levels, while it increased BDKRB2 mRNA expression. Data from a related study show p38K inhibition blocks IL-1β-mediated astrocyte C/EBPβ expression, whereas ERK1/2 inhibition enhances expression [8]. Accordingly, we found that the IL-1β-mediated increase in COX-2 expression is p38K-dependent, whereas IL-1β-mediated expression of BDKRB2 is ERK1/2-dependent.…”
Section: Discussionsupporting
confidence: 60%
“…In human HCC cells, activation of ERK is required for the invasion process [22], and the mechanism is correlated with proteinases and their inhibitors [2325]; thus, we investigated the effect of baicalein on the ERK pathway in MHCC97H cells. Western blotting showed that baicalein could reduce the phosphorylation of ERK1/2 and MEK1 in a concentration-dependent manner (Figure 5A and 5B).…”
Section: Resultsmentioning
confidence: 99%
“…Various pro-inflammatory cytokines upregulate C/EBPβ and C/EBPδ in astrocytes which, together with the effects of LPS, points to a role of C/EBPβ and C/EBPδ in astroglial activation. IL-1β is the most often reported cytokine to upregulate C/EBPβ or C/EBPδ in astrocytes (Fields et al 2013;Fields et al 2011;Kim et al 2004;Li et al 2004;Samuelsson et al 2008). …”
Section: In Vitro Regulation Of C/ebpβ and C/ebpδ Expression: Studiesmentioning
confidence: 99%